Reducing voltage sags through fault current limitation. - Tosato, F.
Short circuit current limitation in distribution utilities can be an effective way to improve power quality, since the expected voltage sag amplitude during faults can be dramatically reduced. A simple series LC circuit tuned at the net frequency, with the capacitor shunted by a metal oxide varistor (MOV), proves to be a well suited limiter to reach the goal. In the paper, the properties of such a circuit are analyzed and its operation is investigated through computer simulation. The relevant pro and con aspects are outlined and discussed
Keywords: Capacitor shunt; Computer simulation; Distribution utilities; Expected voltage sag amplitude; Fault current limitation; Metal oxide varistor; Power quality; Series LC circuit; Short circuit current limitation; Voltage sags reduction